Economic feasibility of irrigation systems in broccoli crop - Fabricio C. de Oliveira; Luciano O. Geisenhoff; Alexsandro C. dos S Almeida; Joaquim A. de Lima Junior; Rogério Lavanholi (Engenharia Agrícola, 2016)
ABSTRACT This study aimed to analyze the economic feasibility of different irrigation systems in broccoli cropping, in Dourados - MS, Brazil. Initially, irrigation was performed using different systems (surface drip, subsurface drip, micro sprinkler, Santeno® and conventional sprinkler). Both yield of commercial inflorescence (CIY) and applied water depth (AWD) were determined during trial. Economic feasibility was analyzed through estimates of acquisition cost (AC), total annual cost (TAC), gross revenue (GR), net revenue (NR), benefit-cost rate (BCR), return rate (RR) and return time (RT). Subsurface drip irrigation was the most feasible in addition to using the second lowest AWD (170.3 mm) compared to the other systems. The values of CIY, AC, RR, BCR and TAC obtained by this system were 25.3 t ha-1, R $ 8,884.8 ha-1, R $ 65,446.9 ha-1 yr-1, 7.3 and 6.32%, respectively.